From soil to canopy: the diversity of adaptation strategies to drought in grapevine - Nathalie Ollat; Marina de Miguel; Clément Saint Cast; Elisa Marguerit; Philippe Vivin; Virginie Lauvergeat; Cornelis van Leeuwen; Sarah J. Cookson; Philippe Gallusci; Gregory A. Gambetta (OENO One)
One of the main consequences of climate change is the increase in frequency and severity of abiotic stresses, which mostly occur in combination. Grapevine, which grows under a wide variety of pedo-climatic conditions, has acquired different adaptive mechanisms during its evolution. Harnessing the genetic diversity of these mechanisms is key to the future adaptation of viticulture to climate change in many traditional wine growing areas. The interactions between scion and rootstock through grafting represent an additional level of diversity and adaptive potential to be explored.